Consumer revolution in north-western Germany: Material culture, global goods, and proto-industry in rural households in the seventeenth to nineteenth centuries - Henning Bovenkerk; Christine Fertig (The Economic History Review, 2022)
Existing scholarship on the early modern consumer revolution postulates a dichotomy between the classic pioneering countries of England and the Netherlands and the remaining parts of Europe, which were more stagnant. We contribute to this literature by analysing probate inventories in a rural area in north-western Germany. We show that a closer look at these spaces, which had an intermediate level of development and integration into global markets, reveals a more gradual development and a discernible market evolution. Sumptuary laws may have somewhat slowed down the change in material culture in German regions, but the presence of towns and the proximity to the Netherlands had noticeably positive effects on consumer behaviour. The proto-industrial orientation of local economies proved to be particularly important, as it led to the granting of access to global markets, in addition to greater availability of cash. We observe a delayed diffusion of the new consumer culture in intermediate European regions and argue for a more gradual view of the European consumer revolution.
Keywords: 330; consumer revolution; consumption; global trade; material culture; north-western Germany; proto-industry